Overview of working fluids and sustainable heating, cooling and power generation technologies - Riffat, Saffa; Aydin, Devrim; Powell, Richard; Yuan, Yijun (Oxford University Press, 2017)
Dependency on energy is much higher than the past and it is clear that energy is vital for a sustainable and safer future. Therefore, urgent solutions are required not only to increase share of renewable resources but also more efficient usage of fossil fuels. This could be achieved with innovative power, air conditioning and refrigeration cycles utilising ‘long-term sustainable’ (LTS) fluids, especially air, water and CO2. In the article we provide a rational approach to the future use of working fluids based on our interpretation of the available technical evidence. We consider it self-evident that volatile fluids will continue to play major roles in cooling and power generation, however, new technologies will be needed that optimise energy efficiency and safety with minimum environmental impact. Concordantly we discuss the past and current situation of volatile fluids and present four innovative technologies using air/water cycles. Study results showed that there is a rapid development in heating, cooling and power generation technologies those use water/air as working fluid. These technologies demonstrate a potential to replace conventional systems, thereby to contribute to global sustainability in near future. However, further development on LTS fluids and materials also process intensification and cost reduction are vital parameters for future advancement of these technologies.